Integrating English Language Education in Village Development, Experiences and Challenges from PTMGRMD 2024 - Ririn Mahriatus Solihat (UNISBA Press, 2024)
Abstract. This research explores the implementation, effects, and benefits of the PTMGRMD program in enhancing English language skills within village communities. Through English language teaching in schools and English Club activities, the program has successfully improved the English language proficiency of village children, utilizing methods like songs, everyday objects, and games. Challenges remain in spelling, but overall, students from various programs participating in the program actively use English, providing a practical environment for village children to practice regularly. The positive impact extends beyond children, benefiting participating students and the village community, instilling confidence in English usage and opening new opportunities for education and employment. Long-term benefits include improved English skills for students and a foundation for further language development, enhancing community well-being. Abstrak. Penelitian ini mengeksplorasi implementasi, dampak, dan manfaat program PTMGRMD dalam meningkatkan keterampilan bahasa Inggris di masyarakat desa. Melalui pengajaran bahasa Inggris di sekolah dan kegiatan Klub Bahasa Inggris, program ini telah berhasil meningkatkan kemampuan bahasa Inggris anak-anak desa, dengan menggunakan metode seperti lagu, benda sehari-hari, dan permainan. Tantangan tetap ada dalam ejaan, tetapi secara keseluruhan, siswa dari berbagai program yang berpartisipasi dalam program ini secara aktif menggunakan bahasa Inggris, menyediakan lingkungan praktis bagi anak-anak desa untuk berlatih secara teratur. Dampak positifnya meluas ke luar anak-anak, menguntungkan siswa yang berpartisipasi dan masyarakat desa, menanamkan kepercayaan diri dalam penggunaan bahasa Inggris dan membuka peluang baru untuk pendidikan dan pekerjaan. Manfaat jangka panjang termasuk peningkatan keterampilan bahasa Inggris bagi siswa dan landasan untuk pengembangan bahasa lebih lanjut, meningkatkan kesejahteraan masyarakat.